2022
DOI: 10.3389/fonc.2022.996329
|View full text |Cite
|
Sign up to set email alerts
|

Integrative proteomics and m6A microarray analyses of the signatures induced by METTL3 reveals prognostically significant in gastric cancer by affecting cellular metabolism

Abstract: METTL3-mediated RNA N6-methyladenosine (m6A) is the most prevalent modification that participates in tumor initiation and progression via governing the expression of their target genes in cancers. However, its role in tumor cell metabolism remains poorly characterized. In this study, m6A microarray and quantitative proteomics were employed to explore the potential effect and mechanism of METTL3 on the metabolism in GC cells. Our results showed that METTL3 induced significant alterations in the protein and m6A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…511 METTL3 has been proved to be upregulated in multiple malignances including GC, 5,1217 and indicate poor prognosis, 5,14,16,17 but it is downregulated and associated with favorable prognosis in RCC. 19 In the present study, in accordance with previous reports, 5,2023 we found that elevated expression of METTL3 was related to poor overall survival, acting as a prognostic marker in GC. METTL3 might be a potential prognostic factor in GC.…”
Section: Discussionsupporting
confidence: 93%
“…511 METTL3 has been proved to be upregulated in multiple malignances including GC, 5,1217 and indicate poor prognosis, 5,14,16,17 but it is downregulated and associated with favorable prognosis in RCC. 19 In the present study, in accordance with previous reports, 5,2023 we found that elevated expression of METTL3 was related to poor overall survival, acting as a prognostic marker in GC. METTL3 might be a potential prognostic factor in GC.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, METTL3 upregulates AVEN and DNAJB1 levels, contributing to a poorer clinicopathological grade and stage in GC patients. These findings suggest that METTL3 influences GC cell metabolism, particularly OXPHOS, and hold promise for developing novel therapeutic targets and predictive markers in GC 457 . Additionally, the upregulation of IGF2BP1 in GC tissues is associated with enhanced aerobic glycolysis and malignant behaviors of GC cells and with a poor prognosis in patients with GC.…”
Section: Rna Methylation and Cancer Metabolismmentioning
confidence: 85%
“…These findings suggest that METTL3 influences GC cell metabolism, particularly OXPHOS, and hold promise for developing novel therapeutic targets and predictive markers in GC. 457 Additionally, the upregulation of IGF2BP1 in GC tissues is associated with enhanced aerobic glycolysis and malignant behaviors of GC cells and with a poor prognosis in patients with GC. In vivo experiments have shown that IGF2BP1 knockdown suppresses the carcinogenesis of GC.…”
Section: Rna Methylation and Cancer Metabolismmentioning
confidence: 99%
“…In GC cells, AGS and HGC27, METTL3, along with the m6A reader HNRNPA2B1, induces the upregulation of nuclear pre-mRNA domain-containing 1B (RPRD1B) with the assistance of lncRNA NEAT1, thereby activating the c-Jun/c-Fos/AP1 pathway and lipid metabolism [ 102 ]. Moreover, an integrative analysis combining proteomics and m6A microarray data has revealed that METTL3 could enhance apoptosis and caspase activation inhibitor (AVEN) and DnaJ heat shock protein family (Hsp40) member B1 (DNAJB1) levels to strengthen oxidative phosphorylation in GC BGC-823 cells [ 103 ]. METTL3 has also been identified as a key player in enhancing BH4 biosynthesis and advancing GC progression through its impact on elevating m6A modification of pre-B-cell leukemia transcription factor 1 (PBX1) mRNA, thereby enhancing GTP cyclohydrolase 1 (GCH1) expression [ 104 ].…”
Section: M6a Regulates Tumor Metabolism In Digestive Tract Tumorsmentioning
confidence: 99%